Numerical study of reinforced concrete slabs under extreme loading conditions: Impact and fire. (October 2019) - Ožbolt, J; Ruta, D; Irhan, B
Abstract: In the present paper, the influence of thermally induced damage of reinforced concrete (RC) slabs on their impact properties are numerically investigated. The RC slabs are first pre-damaged through fire load and then loaded by the impact of hammer. Transient 3D finite element (FE) thermo-mechanical analysis is performed. Subsequently, impact simulation is conducted based on the explicit multi-body dynamic analysis and contact algorithm with adaptive element deletion technique. As a constitutive law for concrete rate and temperature, dependent microplane model is employed. The co-rotational Cauchy stress tensor and Green-Lagrange strain tensor are used in the framework of total Lagrange FE formulation. The numerical results are discussed and compared with those obtained experimentally. It is shown that pre-damage of RC slab through fire reduces the impact resistance of the slabs, and that the simulation is able to realistically replicate the experimental tests.